Are households shifting toward cleaner cooking fuel? Empirical evidence from India during 2005–2021 - Timilsina, Raja Rajendra; Rahut, Dil B.; Gautam, Madhu Sudan; Mishra, Raman; Sonobe, Tetsushi (Frontiers in Environmental Economics, 2023)
Paces of meaningful change vary greatly. Daily usage of fuel, such as electricity, liquid petroleum gas, biogas, kerosene, coal, straw, and dung, for domestic purposes adversely affects the environment, especially in a developing country with a large population like India, where the predominant sources of household cooking fuel are biomass. However, little is known about the trends and patterns of household energy consumption and the factors influencing household energy choices and consumption over the last two decades in India. Many households have changed towards cleaner cooking fuel, such as electricity, LPG, and biogas. This study utilizes the latest National Family Health Survey (NFHS) data from the year 2005/06, 2015/16, and 2019/21 to empirically show that a household’s choice of cleaner energy sources is driven by factors such as gender, education, wealth, social status and location. The study makes it clear that energy choices are context and time specific, such that female-headed households, households with a higher level of education, and upper-income families are more likely to choose cleaner fuels like LPG and electricity. Above all, the marginalized group, scheduled castes, and the poorest family have been struggling continuously for two decades for a clean and cost-effective source of fuel within their proximity, hindering the global effort to attain sustainable development goals (SDG 7).